A new species of Burmissus (Hemiptera: Fulgoromorpha: Mimarachnidae) from mid-Cretaceous Burmese amber. (June 2020) - Luo, Cihang; Jiang, Tian; Wang, Bo; Xiao, Chuantao
Abstract: The eleventh species of Mimarachnidae and the second species of Burmissus is is herein described from mid-Cretaceous Kachin amber. Burmissus szwedoi sp. nov. can be distinguished from the type species Burmissus raunoi Shcherbakov, 2017 by the number of carinae of the mesonotum, tegmen pattern and different broadest portion of the tegmen. Diagnostic features of the genus Burmissus are reviewed. The phylogeny of Mimarachnidae is discussed.